A database on parasitoid of insect pests of crops in Manipur, India (The Journal of Plant Protection Sciences, 2021)
A Parasitoid database consisting of 62 (sixty two) species records gathered by conducting a systematic survey of  parasitoids on insect pests of crops in different localities of Manipur was developed by using MS-Access. The database  is for academic purpose and it includes the taxonomic details of the parasitoid, host insect, host plant, morphological  characters, geographical distribution, period of activity, parasitoid behavior and its biology etc. Image of the parasitoid  species are also provided for helping in easy identification of the species.
Keywords: Database; insect-pest; parasitoids; Manipur